THE MECHANISM OF INCREASING THE FINANCIAL AUTHORITY OF ECONOMIC SUBJECTS THROUGH REGIONAL AGGLOMIRATION CLUSTER - Yusupov Faizulla Yakubovich (American Journals Publishing, 2023)
A mechanism for increasing the financial potential of economic entities through regional agglomeration clusters has been developed. A methodology for improving the agglomeration of production development of economic entities in the region has been developed. The theoretical foundations of production clustering mechanisms in the region have been improved.
Keywords: Digital technology, empirical model, econometric model, forecast results, information system, endogenous variables, exogenous variables.